Pension Reform and the Fiscal Policy Stance - Gerson, Philip (IMF Working Papers; Working Paper ;, 2001)
The increased budget deficit caused by the privatization of a public pension plan does not imply a relaxation of the stance of fiscal policy. The reform's impact on the fiscal stance and national saving depends primarily on its effect on the sum of explicit and implicit public debt and on the post-reform payroll tax and private system contribution rates. However, the precise impact of reform also depends on such influences as the relationship between the rates of interest on implicit and explicit public debt. There may be circumstances in which pension privatization, if not offset by fiscal consolidation, will loosen the fiscal stance.